Implementation of Perforated Concentric Ring Walls Considerably Improves Gas-Liquid Mass Transfer of Shaken Bioreactors - Hansen, Sven; Gumprecht, Andreas; Micheel, Linda; Hennemann, Hans-Georg; Enzmann, Franziska; Blümke, Wilfried (Frontiers in Bioengineering and Biotechnology, 2022)
Since their first use in the 1930s, shake flasks have been a widely used bioreactor type for screening and process development due to a number of advantages. However, the limited gas-liquid mass transfer capacities - resulting from practical operation limits regarding shaking frequency and filling volumes - are a major drawback. The common way to increase the gas-liquid mass transfer in shake flasks with the implementation of baffles is generally not recommended as it comes along with several severe disadvantages. Thus, a new design principle for shaken bioreactors that aims for improving the gas-liquid mass transfer without losing the positive characteristics of unbaffled shake flasks is introduced. The flasks consist of cylindrical glass vessels with implemented perforated concentric ring walls. The ring walls improve the gas-liquid-mass transfer via the formation of additional liquid films on both of its sides, whereas the perforations allow for mixing between the compartments. Sulfite oxidation experiments revealed over 200 % higher maximum oxygen transfer capacities (OTRmax) compared to conventional shake flasks. In batch cultivations of E. coli BL21 in mineral media, unlimited growth until glucose depletion and oxygen transfer rates (OTR) of up to 138 mmol/L/h instead of an oxygen limitation at 57 mmol/L/h as in normal shake flasks under comparable conditions could be achieved. Even overflow metabolism could be prevented due to sufficient oxygen supply without the use of unconventional shaking conditions or oxygen enrichment. Therefore, we believe that the new perforated ring flask principle has a high potential to considerably improve biotechnological screening and process development steps.